AGX Unconference in Nairobi 2025: Catalyzing collaboration and charting a course for Digital Agriculture - DevGlobal (International Food Policy Research Institute, 2025)
This report summarizes the outcomes of the AGX Unconference in Nairobi, Kenya, held on July 23–24, 2025, at the ILRI Conference Center. Co-hosted by CGIAR, the Gates Foundation, GIZ, DIASCA, and DevGlobal, this inaugural gathering convened more than 150 stakeholders—farmers, technologists, researchers, policymakers, and investors—to explore how Digital Public Infrastructure (DPI) and Artificial Intelligence (AI) can drive more efficient, inclusive, and resilient agricultural systems. Designed as a dynamic, participant-driven event, the AGX Unconference prioritized real-world challenges, co-creation, and cross-sector collaboration. Sessions were grounded in farmer and implementer perspectives, highlighting barriers such as fragmented services, inaccessible advisory support, data governance gaps, and underutilized digital tools. In response, working groups and debates examined how DPI and AI can be responsibly leveraged to reduce duplication, improve interoperability, and empower small-scale producers. A central theme throughout the unconference was the need to design systems that are not only technically robust, but also locally relevant, equitable, and built in the public interest. From creating localized AI models to strengthening data infrastructure and inclusive digital ID systems, participants stressed the importance of aligning tools, policies, and partnerships around farmer-centered solutions. The event culminated in the AGX Inspire Challenge, where participants co-developed and pitched actionable, fundable ideas—one of which received seed funding to move forward. The energy and collaboration generated throughout the Unconference underscored the urgency and opportunity of collective action.